(untitled) - Saslow, Joan M (White Plains, 2006)
The student's book contains a bound-in grammar booster, a bound-in pronunciation booster, and student's take-home audio CD that allows students to practice their pronunciation at home or during their commute.
Keywords: English language,English language,Anh ngữ,Anh ngữ; Rhetoric,Tu từ học,Giáo trình dành cho người nước ngoài